IL-15-dependent balance between Foxp3 and RORγt expression impacts inflammatory bowel disease - Milena J. Tosiek (Nature Portfolio, 2016)
Transcription factors directing T cell fate are induced by instructive signals such as cytokines. Here the authors show that IL-15 promotes Foxp3 and inhibits RORγt expression in CD4 T cells, and that IL-15 is critical to suppress colitis by maintaining the Treg to Th1/Th17 ratio in a mouse model.